Comparative evaluation of shear bond strength and failure pattern of three different dentin adhesive systems-An In Vitro Study - Ankita; Paul, Dr. Bonny; Mantri, Shiv Kumar; Dube, Kavita; Akhtar, Farheen; Singh, Niharika; Sinha, Pallavi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Traditionally dentin bonding agents consist of separate components of etchant,primer and adhesive. Advancements in the field of adhesive dentistry have been aimed atreducing technique sensitivity by introducing single-bottle or all-in-one dentin bondingadhesive systems. The purpose of this study was to evaluate the shear bond strength of threeadhesive systems [(G-Bond (GC), Xeno V+ (Dentsply) and Single bond universal (3M)] inregards to buccal surfaces and dentin depth.